Theoretical Analyses of Commodity Tax in an Oligopolistic Market - Kunizaki, Minoru; Nakamura, Kazuyuki; Kakita, Naoki (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents a comprehensive analysis of tax consequences in an oligopolistic market. It provides the reader with a systematic and precise way of understanding the research content of tax incidence. A major feature of the book is its analysis of tax incidence from both domestic and international oligopolies. Then, by examining various oligopoly models, it approaches the essence of domestic and multilateral tax issues. Starting with the general theory of commodity tax incidence in an oligopoly, the topics addressed in this book include tax reform, environmental regulation, and policy coordination in international oligopolies. In addition to the usual oligopoly model, managerial oligopoly, the public pricing problem for firms in an oligopoly, and mixed oligopoly are dealt with. By presenting individual issues and explaining the relevance of each topic, this book is highly recommended for readers interested in policymaking and the global market in relation to the interdisciplinary developments of public economics, regional economics, and international economics. This book is also valuable as an advanced textbook on applied economics.
Chapter 1. Commodity tax incidence in oligopolistic market -- Chapter 2. Comparative Analysis of Specific and Ad Valorem Commodity Taxes: Welfare Analysis of Tax Rate Combination and Optimal Commodity Tax -- Chapter 3. Commodity Tax Incidence in a Labor-managed Firm Oligopoly -- Chapter 4. Managerial Incentives and Principal-Agent Type Oligopoly: Shifting of the Tax Burden -- Chapter 5. Public Pricing and Oligopolistic Market -- Chapter 6. Comparative analysis of environmental regulation and environmental tax -- Chapter 7. Commodity Tax in an International Oligopoly -- Chapter 8. Commodity Tax Harmonization and Global Tariff Reduction with Differentiated International Oligopoly -- Chapter 9. Partial Policy Coordination and Strategic Response in International Oligopoly -- Chapter 10. Privatization Neutrality Theorem in an International Mixed Oligopoly.
Keywords: Regional economics; Spatial economics; Game theory; Industrial organization; Finance, Public; Regional and Spatial Economics; Game Theory; Industrial Organization; Public Economics